kINetic eMOTION: Beyond the object - Vinyu, Alfred (School of Architecture, Planning and Geomatics, 2018)
Challenging the idea of buildings being identified as objects that merely house human experience and inhabitation, this dissertation argues for a "building machine" that adopts the notion of "performative architecture". Programmed as a Film School, kinetic architecture allows the building to be indeterminate whereby the flexibility to reconfigure itself enables a vast potential of spatial narratives. With the use of cinematic techniques the building machine in partnership with people creates multisensory spatial dimensions in what is seen as a continuous architectural carnival.